Optimisation of intra-ply stitch removal for improved formability of biaxial non-crimp fabrics. (15th January 2022) - Chen, S.; Joesbury, A.M.; Yu, F.; Harper, L.T.; Warrior, N.A.
Abstract: Automated fabric forming solutions are required to meet the demand of liquid moulding processes, but wrinkling is a common problem for double-curvature parts due to a combination of the reinforcement type, manufacturing parameters and the part geometry. Local intra-ply stitch removal is introduced in the current work to improve the formability of a pillar-stitched biaxial NCF. An optimisation method is developed to remove stitches selectively, using a genetic algorithm coupled with a finite element model. Two criteria are defined to reduce the occurrence of forming defects whilst maintaining the integrity of the fabric. The first is to minimise the local shear angle across the surface of the ply and the second is to minimise the total stitch removal area. These criteria are combined into a single objective function and validated using a hemisphere forming case study. Experimental results confirm that macro-scale wrinkling can be successfully eliminated when intra-ply stitches are removed according to the optimised pattern. The stitch removal regions are distributed across both the positive and negative shear areas of the optimised NCF blank, indicating that local stitch removal can have a global effect on the formability. Perimeter shapes show that the optimum local stitch removal pattern enables a more balanced global material draw-in, demonstrating that the effect of stitch removal is not limited to the high shear regions. Removing stitches from just the over-sheared regions is therefore insufficient to fully mitigate wrinkles, justifying the need for the optimisation algorithm, as the optimised stitch removal pattern appears to be non-intuitive.